The State as an Actor in International Relations: A View from Realism - Andrade, Alfonsina (2025)
The aim of this article is to analyze the state as an actor in the realist theory of international relations. First, an analysis of the concept of state is made from a historical perspective that allows us to understand the dynamism of the concept. Then the analysis of the role of the state within the realistic theory is carried out comparing its theoretical approaches with current examples of international relations. Finally, it is suggested that, despite the fact that the heyday of realist theory occurred after the Second World War and until the 1970s, the fall of the Twin Towers, the advance of China’s influence in the world and the war between Russia and Ukraine lead us to understand that the struggle for power and influence continue to make states the key players in the international system.